Effect of StudySkills Training on Learning and Study Strategies SelfEfficacy and Satisfaction in Nursing and Midwifery Students Kerman University of Medical Sciences Iran - Esmat Noohi; Nahid Fallahnezhad; Behshid Garoosi; Aliakbar Haghdoost (Kerman University of Medical Sciences, 2014)
Background & Objective: Neglect to the principles study principles has reduced the level of human productivity and efficiency and is a cause of demoralization and loss of selfesteem research boredom and disenchantment Some learning special skills such as methods of receiving storing and recalling the correct content are needed to perform an effective study This study aimed to show the role and impact of academic learning skills and study strategies in improving students study styles and their selfefficacy and satisfaction   Methods: This interventional study using preand posttraining tests was conducted on 75 newentrant nursing and midwifery students of Kerman University of Medical Sciences Iran in 2011 Students completed a researchermade questionnaire including four parts: demographic information learning and study strategies selfefficacy and satisfaction before and after the training The data were analyzed using paired ttest   Results: There were significant difference between the mean pre (105 ± 26) and postintervention (136 ± 18) learning strategies pre (106 ± 18) and postintervention (133 ± 13) study strategies pre (105 ± 32) and postintervention (123 ± 24) selfefficacy and pre (94 ± 34) and postintervention (1208 ± 29) satisfaction scores   Conclusion: Learning and study strategies can be taught and learned Upgrading learning and study strategies increases students sense of selfefficacy and satisfaction According to our results designing a course for training study and learning strategies is suggested to improve college students learning and study skills